Outcomes of Peripheral Vascular Interventions via Retrograde Pedal Access for Chronic Limb-Threatening Ischemia in a Multicenter Registry. (April 2020) - Perry, Mark; Callas, Peter W.; Alef, Matthew J.; Bertges, Daniel J.
Purpose: To describe the use and 1-year outcomes of retrograde pedal access during peripheral vascular interventions (PVI) for chronic limb-threatening ischemia (CLTI).Materials and Methods: From October 2016 to September 2017, 159 patients (mean age 71±10 years; 112 men) undergoing PVI via retrograde pedal access were enrolled in the multicenter Vascular Quality Initiative (VQI) registry. The pedal access approach included retrograde femoral (40%), antegrade femoral (26%), retrograde to antegrade femoral (22%), and pedal only (11%). A comparator group of 1972 patients (mean age 69±12 years; 1129 men) having a contralateral retrograde femoral access was established for propensity matching, which resulted in 156 patients per group. Procedure characteristics, technical success, and access site complications were compared. Major adverse limb events (MALE) and amputation-free survival (AFS) at 1 year were analyzed using the Kaplan-Meier method and Cox proportional hazard models to calculate hazard ratios (HR) and 95% confidence intervals (CI).Results: Technical failure was similar for retrograde femoral and pedal access (7% vs 13%, p=0.07). Complications were rare and included access site hematoma (2 vs 5, p=0.32) and target artery thrombosis (0 vs 2) for the femoral vs pedal access groups, respectively. The rates of MALE at 1 year were significantly lower after retrograde femoral access (24%) compared with pedal access (38%; log-rank p=0.01; HR 1.95, 95% CI 1.15 to 3.30). AFS estimates at 1 year were similar: 86% for retrograde femoral and 83% for pedal access (log-rank p=0.37; HR 1.32, 95% CI 0.73 to 2.39), as were major amputation estimates: 10% for retrograde femoral access and 13% for pedal access group (log-rank p=0.21; HR 1.58, 95% CI 0.77 to 3.26).Conclusion: In this analysis of multicenter registry data, retrograde pedal access in patients with CLTI had similar technical success and early complications in comparison with traditional contralateral retrograde femoral access. The rates of MALE were higher after pedal access but AFS was similar, indicating a tradeoff between limb salvage and repeat interventions.